PENGENDALIAN SEKTOR INFORMAL PADA LAMA PAJANAN KEBISINGAN DENGAN GANGGUAN FUNGSI PENDENGARAN PADA NELAYAN IKATAN NELAYAN SAIJAAN (INSAN) KECAMATAN PULAU LAUT UTARA KOTABARU - Sholihah, Qomariyatus; Setyaningrum, Ratna; Saputra, M.Trisetya Hadi (Universitas Lambung Mangkurat, 2014)
Insan Fishermen most of whole day catch the fish with a ship engine that make a high intensity noise. Based on the beginning of the measurement results found that ship engine noise levelsreach 113 dB. The fishermen work in these conditions 6 to 12 hours a day for an average of more than 5 years. It is very potential to cause hearing loss among fishermen. The purpose of this study is to determine the correlation of length of noise exposure to ward hearing function disorder among Insan fisherman Pulau Laut Utara District Kotabaru. This study uses observational analytic with cross-sectional approach. This study population are fishermen who are members of the Association of Saijaan Fishermen and sampled by random sampling as many as 36 people to look at the table Krejcie (alpha= 5%). The research instruments used in this study are the blank sheet, sound level meter, and a 512 Hz tuning fork. Based on Chi Square test statistics obtained that p-value is 0.002, it means that p-value is less than alpha (0.05) so that Ho is rejected. It can be concluded that there is significant correlation between length of noise exposure to ward hearing function disorder on Insan fishermen. Keywords: noise, length of noise exposure, turning fork, hearing function disorder, fishermen